Understanding second language acquisition - Ortega, Lourdes (New York Routledge, 2013)
The book zooms in and out of universal, individual, and social forces, in each case evaluating the research findings that have been generated across diverse naturalistic and formal contexts for second language acquisition. It assumes no background in SLA and provides helpful chapter-by-chapter summaries and suggestions for further reading.
Keywords: Cơ bản